Not that innocent: a comparative analysis of Canadian, European Union and United States policies on industrial chemicals - Denison, Richard A. (New York, 2007)
"Environmental Defense, in cooperation with Pollution Probe in Canada, has released a major new report on industrial chemicals policies. "Not That Innocent: A Comparative Analysis of Canadian, European Union and United States Policies on Industrial Chemicals" provides — for the first time — a comprehensive comparison of the European Union's new REACH regulation with existing policies in the United States and Canada that govern industrial chemicals.1